Effect of vascular simulation training on practice performance in residents: a retrospective cohort study - Lin Yang; Jianlin Liu; Yanzi Li; Yamin Liu (BMJ Open)
Objective This study aims to investigate the teaching effect of vascular simulation training (ST) in rotating vascular residents.Design Retrospective cohort study.Setting and participants A total of 95 vascular residents were included from 2015 to 2018 in a university affiliated centre western China, and divided into an ST group and a conventional training (CT) group. The ST group received ST and CT, and the CT group only received CT.Primary outcome measures Theoretical scores were assessed, and the technique parameters, complications and radiation damage of the procedures were analysed.Results The mean scores (8.74±1.09 vs 8.13±1.31) and the rate of willingness for retraining (93.62% vs 79.17%) in residents were higher in the ST group than in the conventional training (CT) group (p<0.05). The success rate of arterial puncture was significantly higher in the ST group (78.72% vs 58.33%, p=0.03); however, the incidence of complications was similar between the two groups (p>0.05). The time of the puncture procedure was significantly lower (9.56±5.24 vs 12.15±6.87 min), and the comfort score of the patient (5.49±1.72 vs 4.71±1.57) was higher in the ST group than in the CT group (p<0.05). At the end of the assessment, the learning time for angiography (3.65±0.64 vs 4.07±0.77 months) and the complete procedure time (33.81±10.11 vs 41.32±12.56 min) were lower in the ST group than in the CT group (p<0.01). The fluo time for angiography (489.33±237.13 vs 631.47±243.65 s) and the cumulative air kerma (401.30±149.06 vs 461.16±134.14 mGy) were significantly decreased in ST group (p<0.05).Conclusion The application of a vascular simulation system can significantly improve the clinical performance of residents and reduce the radiation damage from a single intervention procedure in patients.